Third Party Intervention based on Matrix Representation for Conflict Resolution - wang, Jiani; Xu, Haiyan (Advances in Social Sciences Research Journal, 2015)
The model of third part intervention is developed and analyzed using the decision support system (Matrix Representation for Conflict Resolution) (MRCRDSS). MRCR is based on the Graph Model for Conflict Resolution (GMCR) framework that provides a suitable and efficient means to model and analyze a strategic conflict. Until now, a little work has been made on modeling third party interventions. In this paper, the equilibrium state of photovoltaic conflict is identified before and after the intervention of a third party. It is clear to see the third party that involves in a conflict and mediation is most effective.